1994
DOI: 10.1007/bf02303558
|View full text |Cite
|
Sign up to set email alerts
|

Lobular carcinoma in situ: Observation without surgery as an appropriate therapy

Abstract: Four of 51 women treated with observation alone after diagnosis of LCIS developed breast cancer. All were detected by screening at an early stage. LCIS appeared to be an incidental finding on biopsy of mammographic abnormalities. The policy of observation alone for the finding of LCIS spares women mastectomy. Furthermore, cancers that develop in follow-up are likely to be detected at an early stage and be amenable to curative therapy. Observation alone is appropriate treatment for women with LCIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 15 publications
1
24
1
2
Order By: Relevance
“…Whereas LCIS has long been thought not to be associated with any specific mammographic findings, more recent data indicate that calcifications are seen in 21% to 67% of LCIS cases (22)(23)(24). Our observation that increases in LCIS rates over the past 5 years were only observed among women ages 50 to 69 years, the age group of women most likely to receive regular mammograms, supports the notion that these increases are related to changes in mammography utilization rates.…”
Section: Discussionsupporting
confidence: 78%
“…Whereas LCIS has long been thought not to be associated with any specific mammographic findings, more recent data indicate that calcifications are seen in 21% to 67% of LCIS cases (22)(23)(24). Our observation that increases in LCIS rates over the past 5 years were only observed among women ages 50 to 69 years, the age group of women most likely to receive regular mammograms, supports the notion that these increases are related to changes in mammography utilization rates.…”
Section: Discussionsupporting
confidence: 78%
“…32,35 Conventional wisdom holds that LN is an incidental finding in areas adjacent to benign, mammographically detected calcifications and that calcifications are only rarely associated with LN. 24 Carson et al 36 found calcifications in association with LCIS in 21% of mammographically detected lesions (4 of 19), and Crisi et al 32 reported colocalization of calcifications with LN in 41% of cases (12 of 29). In the current study, calcification was the initial mammographic abnormality that prompted core biopsy in 67% of cases in the LN group, compared with 80% of cases in the ADH group.…”
Section: Discussionmentioning
confidence: 99%
“…In many previous studies, calcifications in LCIS were due to dominant lesions in the vicinity of LCIS, rather than LCIS itself. 5,14,15,17 Georgian-Smith and Lawton have reported that LCIS is detected as two types: classic form with punctate calcifications and small, uniform cells, and a second type with pleomorphic calcifications and larger cells associated with central necrosis. 16 In our study, on examination of the two cases that appeared as a mass with microcalcifications, one case contained clustered punctate calcifications, while the other displayed clustered fine pleomorphic microcalcifications.…”
Section: Discussionmentioning
confidence: 97%